Comparação entre coeficientes de difusão derivados do espectro de energia turbulenta e coeficientes de difusão que dependem da razão entre os fluxos de entranhamento e os de superfície - Degrazia, Gervásio Annes (2002)
A most of contaminants turbulent dispersion in Planetary Boundary Layer (CLP) research is related with the concentration turbulent fluxes specification. An approach for these unknown terms allow to solve the diffusion-advection equation. The specification process of concentration turbulent fluxes parameterization is called as closure problem of turbulent transport. The simplest mathematics scheme which lead to a diffusion advection equation solution employ eddy diffusivities that relates the concentration turbulent fluxes to mean concentration gradient. In this work, employing a Eulerian dispersion model and concentration data, eddy diffusivities, derived of turbulent energy spectrum and that which depends of ratio between entrainment and surface fluxes, will be used in superficial concentration field simulation.